Influence of the Month on the Chemical Composition of Mediterranean Italian Buffalo Milk - Vivo, R. De; Napolano, R.; Zicarelli, L. (Journal of Buffalo Science, 2017)
It is known that the chemical composition of milk is influenced by several factors and the length of lactation plays a prominent role. In Italy, where the reproductive activity of the herd is aimed at the demand for milk from the market, the chemical composition is influenced not only by the adoption or otherwise by the out-breeding-mating-strategy (OBMS) but also by the severity which characterise these techniques (the length of the interruption of sexual promiscuity). The productions and the chemical composition of the milk of 23 farms (average 9000 buffaloes a year) were processed from 2011 to August 2016. The milk was daily conferred and analysed. We evaluated the milk production (kg), the percentage of fat, protein, lactose, dairy yield calculated with the equation of Altiero (1989), the values of the titratable acidity (°SH) and of pH. For each parameter, the monthly values of each farm were divided by the respective annual average and were expressed as an index (monthly values/annual average) in order to homogenize the graphical representations.